Neo-Sinus Washout Time Following Transcatheter Aortic Valve Replacement and Hemodynamic Outcomes - Shivabalan Kathavarayan Ramu, MD; Toshiaki Isogai, MD, MPH; Saksham Beotra, MS; Vishwum Kapadia; Nikita Thakore; Ankit Agrawal, MD; Shashank Shekhar, MD; Maryam Muhammad Ali Majeed-Saidan, MD; Rohan Prasad, MD; Agam Bansal, MD; Abdelrahman Abushouk, MD; Odette Iskandar, MD; et al. (Structural Heart)
Background: Leaflet thrombosis and transcatheter heart valve dysfunction are key concerns following transcatheter aortic valve replacement (TAVR). Prolonged neo-sinus washout time (NWT) may predispose patients to hypoattenuated leaflet thickening (HALT) and leaflet thrombosis, increasing the risk of valve degeneration. This study evaluates the association between in vivo NWT derived from aortograms using computer vision and hemodynamic outcomes at 30 days and 1 year post-TAVR. Methods: We retrospectively analyzed 2254 patients (mean age: 79 ​± ​9 years, 40% female) who underwent TAVR with balloon-expandable valves between 2016 and 2020. Patients were tertile stratified into tertile 1 (T1) (1.444-1.870 ​s; n ​= ​752), T2 (1.870-1.939 ​s; n ​= ​752), and T3 (1.939-2.110 ​s; n ​= ​751) based on their NWTs. Results: At 30 days, T3 had a higher transvalvular aortic valve mean gradient than T1 (12.61 ​± ​5.07 mmHg vs. 11.98 ​± ​4.75 mmHg, p ​= ​0.03). In multivariate modeling, T3 was significantly associated with increased aortic valve mean gradient compared to T1 (estimate: 0.703, p ​= ​0.02). NWT was higher in patients with HALT at 30 days (1.970 ​± ​0.047 ​s vs. 1.889 ​± ​0.100 ​s, p ​= ​0.001), with each 0.1 ​second increase in NWT tripling the odds of HALT. Conclusions: Prolonged NWT is associated with higher transvalvular gradients and independently predicts HALT post-TAVR. NWT may serve as a novel marker to identify patients at risk of valve dysfunction and guide early pharmacotherapy.